Microwave dielectric ceramic material with near-zero temperature coefficient of resonance frequency and preparation method thereof

By adding more lithium to microwave dielectric ceramic materials and compounding with Li4Ti5O12 and Mg2TiO4, the problem of insufficient sintering temperature and dielectric performance of existing materials is solved, the improvement of dielectric constant and quality factor and the near-zeroization of the resonant frequency temperature coefficient is achieved, and applications in the field of 5G communications are supported.

CN119551982APending Publication Date: 2025-03-04SUZHOU CERAMIC ELECTRONIC TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411746606.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing microwave dielectric ceramic materials have shortcomings in terms of sintering temperature and dielectric properties, and it is difficult to meet the strict requirements of materials by 5G and 6G technologies, especially in the field of high-frequency communications, the requirements for the temperature stability and dielectric properties of materials are more stringent.

Method used

The lithium volatility of the compound is inhibited by adding lithium, and recombined with Li4Ti5O12 and Mg2TiO4, reducing the sintering temperature, and obtaining a nearly zero resonant frequency temperature coefficient through mutual compensation between positive and negative τf.

Benefits of technology

The dielectric constant εr is achieved between 23 and 27.5, the Q×f value is 36000 and 51400 GHz, the resonance frequency temperature coefficient τf is 0 to 7 ppm/℃, the sintering temperature is 1100 to 1250℃, the high quality factor of the material and the near-zero resonance frequency temperature coefficient are achieved, supporting applications in the field of 5G communications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119551982A_ABST
    Figure CN119551982A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of microwave electronic ceramic materials, in particular to a lithium-based microwave dielectric ceramic material with a near-zero resonant frequency temperature coefficient and a relatively high quality factor and a preparation method thereof. Based on a Li4Ti5O12 and Mg2TiO4 composite system, the lithium element is easy to volatilize at a high temperature (gt, 1000 DEG C), and volatilization of the lithium element can be inhibited by adding a small amount of the lithium element; the material disclosed by the invention is prepared by adopting a solid-phase reaction method, the dielectric constant epsilon r of the material is 23-27.5, the Q * f value is 36000-51400 GHz, and the material has a temperature coefficient of resonance frequency tau f (0-7 ppm / DEG C) close to zero, and shows huge application potential in the field of 5G communication.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of microwave electronic ceramic materials, and in particular to a microwave dielectric ceramic material with a near-zero resonant frequency temperature coefficient and a preparation method thereof. Background Art

[0002] Microwave dielectric ceramics are a type of functional ceramics that act as dielectric materials in microwave frequency band circuits. They have unique electromagnetic properties and are widely used in communications, navigation, radar, satellites and other fields.

[0003] With the development of 5G and 6G technologies, higher requirements are placed on the performance of microwave dielectric ceramics, especially in the field of high-frequency communications, where the requirements for the dielectric constant, quality factor and temperature stability of the materials are more stringent. Such materials are usually required to have high Q × f value, low dielectric loss and near-zero resonant frequency temperature coefficient to ensure the stability and transmission efficiency of communication signals.

[0004] Since Mg2TiO4, a spinel structure microwave dielectric ceramic, usually has low dielectric loss, it has attracted widespread attention. Belous et al. (Belous A, Ovchar O, Durilin D, et al. High-Q Microwave Dielectric Materials Based on the Spinel Mg2TiO4[J]. Journal of the American Ceramic Society, 2006, 89(11): 3441-3445.) first studied the spinel structure microwave dielectric ceramic with extremely high dielectric loss. Q × f The best microwave dielectric properties of spinel Mg2TiO4 sintered at 1450℃ are: e r = 14, Q × f = 150000GHz, t f = -50 ppm / ºC, Huang et al. (Huang CL, Liu SS Low-loss microwavedielectrics in the (Mg 1−x Zn x )2TiO4 ceramics[J]. Journal of the American CeramicSociety, 2008, 91(10): 3428-3430.) By Zn 2+ Replace Mg2+ The best microwave dielectric properties obtained under sintering at 1330°C are: e r = 15.48, Q × f = 275300 GHz, t f = -34 ppm / ºC, Liu S., Li H., Xiang R., et al. Effect of substituting Al 3+ for Ti 4+ on the microwave dielectric performance of Mg2Ti 1-x Al 4 / 3x O4 (0.01 ≤ x ≤ 0.09) ceramics[J].Ceramics International, 2021, 47(23): 33064-33069.) 3+ Replace Ti 4+ The best microwave dielectric properties obtained under sintering at 1420°C are: e r = 14.65, Q × f = 182347 GHz, t f = -57.7 ppm / ºC, Li H., Tang B., Li Y., et al. Relationships between Sn substitution for Ti and microwave dielectric properties of Mg2(Ti 1−x Sn x )O4 ceramics system[J]. Journal of Materials Science: Materials in Electronics, 2015, 26(1):571-577.) by Sn 4+ Replace Ti 4+ The best microwave dielectric properties obtained under sintering at 1510°C are: e r = 12.18, Q × f = 170130 GHz, t f= -51.7 ppm / ºC, but these materials have higher sintering temperatures and larger negative values t f , but difficult to be applied in practice.

[0005] Therefore, it is necessary to develop a low-cost and easy-to-prepare material with high quality factor and near-zero t f materials is an urgent problem that needs to be solved. Summary of the invention

[0006] In view of the above problems of microwave dielectric ceramic materials in sintering temperature and dielectric properties, the present invention provides a microwave dielectric ceramic material with a resonance frequency temperature coefficient of near zero and a preparation method thereof. The dielectric constant of the material of the present invention is e r 23~27.5, Q × f The value is 36000~51400 GHz, t f The value is 0-7 ppm / °C, and the sintering temperature is 1100-1250°C; these characteristics indicate that the lithium-based material of the present invention has significant application potential in the field of microwave communications and can support the further development and innovation of communication technology.

[0007] The present invention suppresses the volatilization of lithium element in the compound by adding more lithium, so as to achieve the purpose of improving microwave dielectric properties, and then Li4Ti5O 12 Combined with Mg2TiO4 to reduce the sintering temperature and through positive and negative t f The mutual compensation results in a near-zero resonant frequency temperature coefficient.

[0008] To achieve the above effect, the present invention preferentially prepares Li 4(1+x) Ti5O 2(6+x) Raw materials and Mg2TiO4 raw materials, and then the two are compounded in a 1:1 molar ratio to finally obtain Li 2(1+x) MgTi3O (8+x) materials.

[0009] The optimal solution is x = 0.005, and the obtained microwave dielectric ceramic material has the following micro-dielectric properties: e r = 26.1, Q × f = 51400 GHz, t f = 6.08 ppm / ℃, sintering temperature is 1175℃.

[0010] The specific preparation steps of the microwave dielectric ceramic material of the present invention are as follows: Step 1: weigh the raw materials Li2CO3 and TiO2 respectively in a molar ratio of (2+2x) : 5 and form a mixture, wherein 0≤x≤0.01; then add anhydrous ethanol to the mixture in a mass ratio of powder to anhydrous ethanol of 1: 1-2, and perform ball milling to ensure uniform mixing; the speed of the ball mill is controlled at 240-300 rpm, and the ball milling time is 6-10 h; after the ball milling is completed, the obtained slurry is dried at 100° C. to obtain the desired dry powder; Step 2: The powder obtained in step 1 is sieved through a 60-mesh sieve, heated to 700-950°C at a heating rate of 1-5°C / min for pre-sintering, and kept at this temperature for 2-6 h, and then cooled naturally to obtain the pre-sintered Li 4(1+x) Ti5O 2(6+x) Powder; Step 3: weigh the raw materials MgO and TiO2 at a molar ratio of 2:1 and form a mixture, then add anhydrous ethanol to the mixture at a mass ratio of powder to anhydrous ethanol of 1:1-2, and perform ball milling to ensure uniform mixing; the speed of the ball mill is controlled at 240-300 rpm, and the ball milling time is 6-10 h; after the ball milling is completed, the obtained slurry is dried at 100°C to obtain the desired dry powder; Step 4: The powder obtained in step 3 is sieved through a 60-mesh sieve, heated to 1000-1200°C at a heating rate of 1-5°C / min for pre-sintering, and the heat preservation time is 2-6 hours, and then naturally cooled to obtain a pre-sintered Mg2TiO4 powder; Step 5: Follow the Li 2(1+x) MgTi3O (8+x) The pre-calcined powders obtained in step 2 and step 4 are weighed and mixed, wherein 0≤x≤0.01; then anhydrous ethanol is added to the mixture at a mass ratio of 1:1-2 between the powder and anhydrous ethanol, and ball milling is performed to ensure uniform mixing; the speed of the ball mill is controlled at 240-300 rpm, and the ball milling time is 6-10 hours; after the ball milling is completed, the obtained slurry is dried at 100°C to obtain the desired dry powder; Step 6: The powder obtained in step 5 is sieved through a 60-mesh sieve, then mixed with a 5-15 wt% polyvinyl alcohol (PVA) solution, granulated, sieved through a 40-mesh sieve, and dry-pressed at a pressure of 5-10 MPa to form a desired green body; Step 7: placing the green body prepared in step 6 into a sintering furnace, heating the temperature to 400-600°C at a heating rate of 1-5°C / min for debinding treatment, keeping the temperature for 2-6 hours, and then cooling naturally to obtain a green body after debinding; Step 8: Place the green body obtained in step 7 into a sintering furnace, heat it to 1100-1250°C at a heating rate of 1-5°C / min for sintering, keep it warm for 2-6 hours, and then cool it naturally to obtain a microwave dielectric ceramic material with a resonant frequency temperature coefficient of near zero.

[0011] In the above preparation steps, the present invention adopts Li4Ti5O 12 A small amount of Li2CO3 is added to prevent the volatilization of lithium elements, and then compounded with Mg2TiO4 to reduce its sintering temperature and adjust its resonant frequency temperature coefficient to zero. Moreover, as the amount of Li2CO3 increases, its quality factor can be effectively improved.

[0012] The microwave dielectric ceramic material prepared by the present invention has low raw material cost and is environmentally friendly. The preparation method is a solid phase method, the ball milling medium used is a zirconia ball, the process is simple, and the processing is easy. The sintering temperature of the material is relatively low, 1100-1250°C. e r = 23~27.5, Q × f The value (36000~51400 GHz) is relatively high and the resonant frequency temperature coefficient (0~7 ppm / ℃) is stable and close to zero, which has great application prospects in the field of 5G communications. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 Li is sintered at 1175℃ 2(1+x) MgTi3O (8+x) XRD pattern of Figure 2 Li is sintered at 1175℃ 2(1+x) MgTi3O (8+x) Microwave dielectric properties diagram. DETAILED DESCRIPTION

[0014] The specific implementation of the present invention is further described below in conjunction with the accompanying drawings and embodiments. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and cannot be used to limit the protection scope of the present invention.

[0015] The technical solutions specifically implemented in the present invention are as follows: The present invention provides a microwave dielectric ceramic material with a near-zero resonant frequency temperature coefficient, which is prepared by the following steps: Step 1: weigh the raw materials Li2CO3 and TiO2 respectively in a molar ratio of (2+2x) : 5 and form a mixture, wherein 0≤x≤0.01; then add anhydrous ethanol to the mixture in a mass ratio of powder to anhydrous ethanol of 1:1.5, and perform ball milling to ensure uniform mixing; the speed of the ball mill is controlled at 280 rpm, and the ball milling time is 8 h; after the ball milling is completed, the obtained slurry is dried at 100°C to obtain the desired dry powder; Step 2: The powder obtained in step 1 was sieved through a 60-mesh sieve, heated to 900°C at a heating rate of 3°C / min for pre-sintering, kept at this temperature for 4 h, and then cooled naturally to obtain the pre-sintered Li 4(1+x) Ti5O 2(6+x) Powder; Step 3: weigh the raw materials MgO and TiO2 at a molar ratio of 2:1 and form a mixture, then add anhydrous ethanol to the mixture at a mass ratio of powder to anhydrous ethanol of 1:1.5, and perform ball milling to ensure uniform mixing; the speed of the ball mill is controlled at 280 rpm, and the ball milling time is 8 h; after the ball milling is completed, the obtained slurry is dried at 100°C to obtain the desired dry powder; Step 4: The powder obtained in step 3 is sieved through a 60-mesh sieve, heated to 1100°C at a heating rate of 3°C / min for pre-sintering, kept at this temperature for 4 h, and then cooled naturally to obtain pre-sintered Mg2TiO4 powder; Step 5: Follow the Li 2(1+x) MgTi3O (8+x) The pre-calcined powders obtained in step 2 and step 4 are weighed and mixed, wherein x = 0 to 0.01; then anhydrous ethanol is added to the mixture at a mass ratio of 1:1.3 between the powder and anhydrous ethanol, and ball milling is performed to ensure uniform mixing; the speed of the ball mill is controlled at 280 rpm, and the ball milling time is 6 h; after the ball milling is completed, the obtained slurry is dried at 100°C to obtain the desired dry powder; Step 6: The powder obtained in step 5 was sieved through a 60-mesh sieve, then mixed with a 5 wt% polyvinyl alcohol (PVA) solution, granulated, sieved through a 40-mesh sieve, and dry-pressed at a pressure of 5 MPa to form a cylindrical body with a diameter of 16 mm and a thickness of 8 mm; Step 7: Place the green body prepared in step 6 into a sintering furnace, heat it to 550°C at a heating rate of 3°C / min for debinding treatment, keep it at that temperature for 4 hours, and then cool it naturally to obtain a green body after debinding; Step 8: Place the green body obtained in step 7 into a sintering furnace, heat it to 1100-1250°C at a heating rate of 3°C / min for sintering, keep it warm for 4 hours, and then cool it naturally to obtain a microwave dielectric ceramic material with a resonant frequency temperature coefficient of near zero.

[0016] The specific embodiment selected values ​​of x as 0, 0.0025, 0.005, 0.0075 and 0.01; like Figure 1 , is the XRD spectrum corresponding to different x values ​​when the specific embodiment is sintered at a temperature of 1175°C; Figure 1 It can be seen that the sample is the characteristic peak of Li2MgTi3O8 phase; like Figure 2 , is the specific embodiment sintered at a temperature of 1175°C, the corresponding values ​​of different x e r value, Q × f Value and t f Value, from Figure 2 It can be seen from the figure that when x = 0~1, the microwave dielectric properties change. e r = 23~27.5, Q × f = 36000~51400 GHz, t f = 0~7 ppm / ℃, and when x = 0.005, e r = 26.1, Q × f = 51400GHz, t f = 6.08 ppm / °C.

[0017] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A microwave dielectric ceramic material with a near-zero resonant frequency temperature coefficient, characterized in that: Li4Ti5O 12 With Mg2TiO4, a composite system is formed. By adjusting the amount of lithium added, a group of chemical formulas is obtained: Li 2(1+x) MgTi3O 8+x Material, only Li2MgTi3O8 single phase exists in the system; among them, 0≤x≤0.

01.

2. The microwave dielectric ceramic material with a near-zero resonant frequency temperature coefficient according to claim 1, characterized in that: The x is 0.

005.

3. The method for preparing the microwave dielectric ceramic material according to claim 1, characterized in that: The microwave dielectric ceramic material is prepared by a solid phase reaction method, which specifically includes the following steps: Step 1: weighing raw materials Li2CO3 and TiO2 respectively in a molar ratio of (2+2x) : 5 and forming a mixture, wherein 0≤x≤0.01; then adding anhydrous ethanol to the mixture in a mass ratio of powder to anhydrous ethanol of 1:1-2, and ball milling to ensure uniform mixing; after ball milling, drying the obtained slurry to obtain the desired dry powder; Step 2: The powder obtained in step 1 is sieved through a sieve, pre-burned at a high temperature, kept at a certain temperature for a certain period of time, and then cooled naturally to obtain the pre-burned Li 4(1+x) Ti5O 2(6+x) Powder; Step 3: weighing raw materials MgO and TiO2 at a molar ratio of 2:1 respectively to form a mixture, then adding anhydrous ethanol to the mixture at a mass ratio of powder to anhydrous ethanol of 1:1-2, and ball milling to ensure uniform mixing; after ball milling, drying the obtained slurry to obtain the desired dry powder; Step 4: sieve the powder obtained in step 3 through a sieve, pre-sinter at a high temperature, keep the temperature for a certain period of time, and then cool naturally to obtain pre-sintered Mg2TiO4 powder; Step 5: Follow the Li 2(1+x) MgTi3O (8+x) The pre-calcined powders obtained in step 2 and step 4 are weighed and mixed respectively, wherein 0≤x≤0.01; then anhydrous ethanol is added to the mixture at a mass ratio of 1:1-2 between the powder and anhydrous ethanol, and ball milling is performed to ensure uniform mixing; after ball milling, the obtained slurry is dried to obtain the desired dry powder; Step 6: The powder obtained in step 5 is sieved through a sieve, then mixed with a 5-15 wt% polyvinyl alcohol solution, granulated, sieved through a 40-mesh sieve, and dry-pressed at a pressure of 5-10 MPa to form a desired green body; Step 7: placing the green body prepared in step 6 into a sintering furnace, heating it up for debinding treatment, keeping it warm for a certain period of time, and then cooling it naturally to obtain a green body after debinding; Step 8: Place the green body obtained in step 7 into a sintering furnace, heat it up for sintering, keep it warm for a certain period of time, and then cool it naturally to obtain a microwave dielectric ceramic material with a resonant frequency temperature coefficient close to zero.

4. The method for preparing a microwave dielectric ceramic material according to claim 3, characterized in that: In step 1, step 3 and step 5, the rotation speed of the ball mill is controlled at 240 to 300 rpm, and the ball milling time is 6 to 10 h.

5. The method for preparing a microwave dielectric ceramic material according to claim 3, characterized in that: In step 2, step 4 and step 6, sieve through a 60-mesh sieve.

6. The method for preparing a microwave dielectric ceramic material according to claim 3, characterized in that: In step 2, step 4, step 7 and step 8, the insulation time is 2 to 6 hours.

7. The method for preparing a microwave dielectric ceramic material according to claim 3, characterized in that: In step 1, step 3 and step 5, the obtained slurry is dried at 100°C.

8. The method for preparing a microwave dielectric ceramic material according to claim 3, characterized in that: In step 2, the temperature is raised to 700-950° C. at a heating rate of 1-5° C. / min for pre-sintering; In step 4, the temperature is raised to 1000-1200° C. at a heating rate of 1-5° C. / min for pre-sintering.

9. The method for preparing a microwave dielectric ceramic material according to claim 3, characterized in that: In step 7, the temperature is raised to 400-600° C. at a heating rate of 1-5° C. / min for debinding treatment, kept at the temperature for a certain period of time, and then cooled naturally to obtain a debinded green body; In step 8, the temperature is raised to 1100-1250° C. at a heating rate of 1-5° C. / min for sintering.

10. The method for preparing a microwave dielectric ceramic material according to claim 3, characterized in that: First, prepare Li with different lithium contents 4(1+x) Ti5O 2(6+x) and Mg2TiO4, and then synthesize Li 2(1+x) MgTi3O (8+x) .

Citation Information

Patent Citations

  • Microwave medium ceramic material with low-temperature sintering spinel structure and preparation method thereof

    CN101786875A

  • Dielectric constant microwave dielectric material used in low-temperature sintering and preparation method thereof

    CN107056277A

  • Microwave dielectric material with near-zero temperature coefficient of resonance frequency and preparation method thereof

    CN114031393A

  • Electrode laminated body, sintered body, and manufacturing method thereof

    JP2020071948A